Muhammadiyah's Political Dialectics in Partai Amanat Nasional: Elite Dynamics and Structural Accommodation - Rahmayanti; Siregar, Burhanuddin (Analisis: Jurnal Studi Keislaman, 2025)
Muhammadiyah has a tradition of maintaining political independence as a civil society organization, while simultaneously playing an active role in Indonesian national life. In the post-reform context, the involvement of Muhammadiyah elites in PAN presents a dialectic between the principle of organizational neutrality, the dynamics of political elites, and the practice of structural accommodation within the party. This relationship is important to examine to understand the patterns of interaction between civil society organizations and political parties in Indonesia's democratic system. This study uses a qualitative descriptive design with the aim of clarifying in depth, detail, and intensively Muhammadiyah's political activities and movements within PAN. Data are analyzed through the paradigms of civil society and political party relations. This approach is strengthened by the theory of political relations as the main framework and the theory of the relationship between religion and state as a supporting foundation. The results show that Muhammadiyah's neutral stance towards political parties, as decided at the 38th Congress in Makassar in 1971, continues to be maintained. In post-reform political practice, Muhammadiyah views PAN as a strategic partner through collaborative or participatory relations. PAN implements a structural accommodation strategy by involving Muhammadiyah cadres in the central level management of around thirty percent, as well as cultural accommodation through religious, educational and social activities that are in line with the party's Articles of Association, while simultaneously carrying out the functions of communication, political education and controlling social conflict.